The antimicrobial and antibiofilm properties of allicin against Candida albicans and Staphylococcus aureus - A therapeutic potential for denture stomatitis - Mukarramah Zainal; Nurhayati Mohamad Zain; Indah Mohd Amin; Vivi Noryati Ahmad (Elsevier, 2021)
The objective of this study is to determine the therapeutic efficacy of allicin against Candida albicans (C. albicans) and Staphylococcus aureus (S. aureus), the common etiological agents for denture stomatitis (DS). The minimum inhibitory concentration (MICs), minimum bactericidal concentrations (MBCs) and minimum fungicidal concentration (MFCs) of allicin were determined by the broth microdilution method followed by checkerboard microdilution method for a synergistic interaction between allicin + nystatin and allicin + CHX. The potential of allicin to eradicate C. albicans and S. aureus biofilms was assessed by treating biofilm formed on self- polymerized acrylic resin with allicin at a sub-MIC concentration for 5 min. The commercial denture cleanser (brand X) was used as a positive control. A Kruskal-Wallis test followed by the post-hoc Mann-Whitney U test was applied (SPSS 20.0), and the level of significance was set at P < 0.05. Allicin exhibited antimicrobial activity against C. albicans (MIC:8 µg/ml and MFC:16 µg/ml) and S. aureus (MIC:8 µg/ml and MBC:8 µg/ml). A synergistic interaction was observed between allicin + nystatin and allicin + CHX (FICI ≤ 0.5). Allicin exhibited significant biofilm eradication against C. albicans and S. aureus biofilms with percentages of 50.0% and 52.6%, respectively. The results of this study suggest a possible application of allicin in treating C. albicans and S. aureus infection in DS.